Oxidative Stress Biomarkers and Chondrocyte Apoptosis as Predictors of Postoperative Outcomes in Osteonecrosis of the Femoral Head: Oxidative Stress Biomarkers in ONFH Recovery - HU, CHIA-JUI; Song, Ming; Yu, Lai; Zeng, Guanfei (Journal of Medical Biochemistry, 2025)
Background: Osteonecrosis of the femoral head (ONFH) is a progressive disease where oxidative stress and chondrocyte apoptosis contribute to cartilage degeneration and postoperative complications. Identifying reliable biochemical markers is essential for prognosis after hip resurfacing arthroplasty (HRA).Methods: A retrospective analysis was conducted in 134 ONFH patients (ARCO stage II–III) treated with HRA. Serum oxidative stress markers—reactive oxygen species (ROS), superoxide dismutase (SOD), and malondialdehyde (MDA)—were measured preoperatively and at serial postoperative timepoints. Chondrocyte apoptosis rates were assessed by flow cytometry. Pain and functional recovery were evaluated using VAS and Harris hip scores. Correlation, univariate, and Cox regression analyses were applied to determine associations with postoperative outcomes.Results: Patients with high oxidative stress had significantly increased ROS and MDA levels, reduced SOD activity, and elevated chondrocyte apoptosis (P
Keywords: Osteonecrosis of the femoral head; oxidative stress; biomarkers; chondrocyte apoptosis; prognosis; medical biochemistry